Step-by-step explanation:
there are 3 ways to solve SAS triangle
first figure out [tex]\angle C [/tex]
to do so we will use the formula of law of cosine of C angle
[tex] {c}^{2} = {a}^{2} + {b}^{2} - 2ab.\cos(C) [/tex]
substitute the given values of a,b and [tex]\angle C[/tex]
[tex] \sf{c}^{2} = {6 }^{2} + {3.5}^{2} - 2.6.(3.5). \cos( {25.7}^{ \circ} ) [/tex]
simplify squares:
[tex]c^{2}=36+12.25-42.\cos(25.7^{\circ})[/tex]
simplify addition:
[tex]c^{2}=48.25-42.\cos(25.7^{\circ})[/tex]
square root both sides
[tex] \sf \: \sqrt{ {c}^{2} } = \sqrt{ 48.25-42. \cos(25.7^{\circ})}[/tex]
simplify:
therefore
[tex]\bold{c=3.23}[/tex]
use law of sine to figure out angle A
[tex] \dfrac{6}{\sin( \angle \: A) } = \dfrac{3.23}{\sin(25.7)} [/tex]
therefore
[tex]\bold{\angle A=53.66°}[/tex](use calculater to simplify it)
therefore
[tex]\angle B\: is\: 180^{o}-25.70^{o}-53.66^{o}[/tex]
[tex]\bold{= 100.64}[/tex]